2010
DOI: 10.3928/01477447-20091124-30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tranexamic Acid on Reducing Blood Loss in Cementless Total Hip Arthroplasty Under Epidural Anesthesia

Abstract: Total hip arthroplasty (THA) is associated with high intraoperative and postoperative blood loss. Antifibrinolytic drugs have been used to minimize the potential risks of bleeding and blood transfusion. Studies on the effect of tranexamic acid on decreasing blood loss in THA have revealed interesting results, but most have focused on cemented THA. Yet its benefits in THA, especially in cementless THA, have not been proved. We conducted a prospective double-blind randomized controlled study on 64 patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 35 publications
1
47
0
1
Order By: Relevance
“…Out of the 33 studies, one was triple-blind [24], 24 were double-blind [2,4-6,8,11,12,14,17,18], [20,25-37], three were single-blind [19,38,39], and in five studies the blinding was unclear [3,40-44]. Additionally, 21 studies had a Jadad score greater than three [2,4-6,11,12,14,17-19,24-27,31], [33-38] indicating they were of high quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 33 studies, one was triple-blind [24], 24 were double-blind [2,4-6,8,11,12,14,17,18], [20,25-37], three were single-blind [19,38,39], and in five studies the blinding was unclear [3,40-44]. Additionally, 21 studies had a Jadad score greater than three [2,4-6,11,12,14,17-19,24-27,31], [33-38] indicating they were of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Tranexamic acid (TXA) is a synthetic amino acid [2-4,6,9,12,14-16] which competitively blocks the lysine binding sites on plasminogen and thereby slows the conversion of plasminogen to plasmin [2,3,5-8,10,12,14-20]. TXA may be administered intra-venous (IV) or topically in the surgical wound.…”
Section: Introductionmentioning
confidence: 99%
“…Not only does cell salvage reduce allogeneic transfusion requirements, it may also increase survival after oesophagectomy when compared with allogeneic blood transfusion [59]. The use of antifibrinolytic agents has been shown to reduce blood loss during cardiac, urologic and orthopaedic procedures [60].…”
Section: Blood Transfusionmentioning
confidence: 99%
“…A large number of studies 4,7,9,10,12,16,26 discuss the cost-effectiveness of different intravenous tranexamic acid protocols; however, intra-articular use limits the dose required, and thus the cost, making its use more significant. This is because only a small portion of the drug reaches the target location when injected intravenously; therefore, intra-articular administration would provide a more efficient method of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies have shown the effectiveness of intravenous tranexamic acid use on reducing blood loss in THA. [4][5][6][7][8][9][10][11][12][13][14][15] However, concerns about the safety of the systemic administration of tranexamic acid and the risk of thromboembolic events, such as deep vein thrombosis or pulmonary embolism, in the high-risk THA patient population have hindered the wide adoption of this medication in the setting of total joint arthroplasty. In view of such safety concerns, intraarticular injection of tranexamic acid during THA may be a safer route of administration that will reduce postoperative bleeding while not increasing the hypercoagulable state associated with THA.…”
mentioning
confidence: 98%